Rupture of the spleen in a patient with a perforated duodenal ulcer and infectious mononucleosis. Issue 627 (January 1978) - Gray, Robin
Abstract : A 72-year-old patient presented as a sealed perforated duodenal ulcer. This was later confirmed at operation when in addition a haemoperitoneum due to a lacerated friable spleen was discovered. The patient denied antecedent injury. The peripheral blood film was normal but a subsequent differential slide test for infectious mononucleosis was positive. Histology of the spleen showed hyperplasia of the red pulp in addition to capsular and trabecular infiltration with lymphocytes and atypical mononuclear cells confirming the diagnosis. Infectious mononucleosis in the elderly is rare and a complicating rupture of the spleen at this stage has not been reported previously. The diagnosis may depend on the histology alone because the peripheral blood film and serology can be negative. The possible role of the perforated duodenal ulcer is discussed.